Development of the social media privacy protection skills scale for adolescents - Gelbal Odabaş, Özlem; İlhan, Tahsin and Kılıçer, Kerem (Journal of Dependence, 2021)
Objective: The aim of the study is to develop a valid and reliable scale in which adolescents privacy protection skills can be evaluated. Method: The research was conducted with a total of 790 secondary and high school students (F: 435, M: 355) between the ages of 11-18. In order to form the item pool, individual interviews were conducted with 10 students (F: 5, M: 5) between the ages of 15-18. In the collection of data, Social Media Privacy Protection Skills Scale for Adolescents, Online Privacy Scale-Online Security Scale developed as sub-dimensions of Student Cyber Health Scale were used. Results: As a result of the factor analysis, it was observed that the total variance explained by the scale with 27 items was 46.33%, it displayed a three-factor structure, and the fit indices of the first and second level confirmatory factor analysis indicated good fit. The correlation values obtained as a result of the criterion-based validity studies conducted with the online privacy scale and the online security scale support the validity of the scale. The Cronbach Alpha coefficient is .90 and test-retest reliability coefficient is .78 for the whole scale. Conclusion: Social Media Privacy Protection Skills Scale for Adolescents is thought to be a valid and reliable measurement tool and can be used to measure social media privacy protection skills variable.